2014
DOI: 10.1155/2014/923717
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Hip Fractures and Inpatient Services: Predicting Hospital Charges Using the ASA Score

Abstract: Purpose. To determine if the American Society of Anesthesiologist (ASA) score can be used to predict hospital charges for inpatient services. Materials and Methods. A retrospective chart review was conducted at a level I trauma center on 547 patients over the age of 60 who presented with a hip fracture and required operative fixation. Hospital charges associated with inpatient and postoperative services were organized within six categories of care. Analysis of variance and a linear regression model were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This leads to an increase in the percentage of geriatric hip fractures and subsequently an increase in the growth of health care costs. Moreover, the total cost is burdened with other factors, such as longer recovery periods, postoperative complications and comorbidities, and prolonged hospital stay [ 17 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This leads to an increase in the percentage of geriatric hip fractures and subsequently an increase in the growth of health care costs. Moreover, the total cost is burdened with other factors, such as longer recovery periods, postoperative complications and comorbidities, and prolonged hospital stay [ 17 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the abovementioned information, the need for a risk-adjusted reimbursement system arises. The US government uses the ASA classification system as a risk-adjustment tool, which identifies the patients' factors that help predict the hospitalization costs [ 20 , 21 ]. In addition, apart from the cost-morbidity correlation, the overall patients' health status and their postoperative condition constitute important factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Highquality economic studies have evaluated the benefits of directing resources toward the focused goal of reducing time to the operating room [19] and the benefits of early initiation of osteoporosis treatment [31,32,35]. Additionally, numerous studies have identified important predictors of perioperative complications, costs, and mortality [5,13,18,41,46,49,53,54,65], suggesting that different patient populations may have different predisposing risk factors, and thus experience different degrees of benefit from a comanagement system. Although the financial issues associated with comanagement programs have been explored [14,19,37], to our knowledge no formal economic analysis based on decision analysis principles-which can be used to synthesize results over multiple studies and create generalizable conclusions-has been performed.…”
Section: Introductionmentioning
confidence: 99%